Near Is My Shirt but Nearer Is My Skin. Ideology or Self-Interest as Determinants of Public Opinion on Fiscal Policy Issues - Hans Pitlik; Gerhard Schwarz; Barbara Bechter; Bernd Brandl (Austrian Institute of Economic Research (WIFO), 2010)
Several empirical studies derive that personal positions with respect to policy measures are dominated by ideology instead of narrow self-interest. In the present field study we carried out a telephone survey with 1,003 respondents all over Austria. Instead of measuring selfishness indirectly by using more or less "objective indicators" for self-interest, we requested respondents to assess directly whether they expect to be affected by policy measures. Our results indicate that such a subjectively measured narrow self-interest explains attitudes towards economic policies at least as good as ideological conviction. In some cases ideology appears to determine whether people feel affected by a proposed policy measure.
Keywords: 330; Finanzpolitik; Öffentliche Meinung; Eigeninteresse; Ideologie; Befragung; Österreich